Collaborative learning effects when students have complete or incomplete knowledge. Issue 6 (13th August 2018) - Retnowati, Endah; Ayres, Paul; Sweller, John
Summary: Cognitive load theory was used to hypothesize that the effectiveness of collaborative learning is moderated by the completeness of the prerequisite knowledge bases of group members. It was predicted that when group members have gaps in their knowledge base that can be filled by other group members, collaborative is superior to individual learning. In contrast, if group members have no prerequisite knowledge gaps, then collaborative learning is redundant and as a consequence inferior to individual learning. To test these, 58 grade 7 Indonesian students were randomly assigned to work collaboratively or individually on intermediate mathematics problems, with either full knowledge or gaps in their knowledge base. The results indicated that with gaps, collaboration led to superior learning. However, with a more complete knowledge, individual learning was superior to collaborative learning due to redundancy effects. The results suggest that collaboration does not always lead to superior learning compared with individual study.